IMPLEMENTASI RTRW KOTA TANGERANG SELATAN DAN TANTANGAN MASA DEPAN - -, Achmad Sjafrudin (Bulletin of Scientific Contribution, 2013)
To depelop region could be give positif and negatif impact to the environment.Case studies give example could be impact to the soil, land and space in this area. In the implementation regulation of the Perda No. 15 , Year 2011-2031 should be followed by all stakeholder on the development planing in those area. The regulation guide the fuction in the pasal 2, as operational tool development in South Tangerang. The other words we call instrument guide sustainable development.